Pengembangan Sistem Informasi Pengelolaan Nilai Hasil Belajar Murid dan Pendaftaran Murid Baru pada Madrasah Tsanawiyah Ma'arif Udanawu Blitar - Daniel Sri Bintang; Ismiarta Aknuranda; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Madrasah Tsanawiyah Ma'arif Bakung is an Islamic junior high school located in Blitar Regency. Each new academic year, the number of new students can reach 300 students with the number of educators teaching as many as 60 people. With so many students being accommodated, the value management process to become a report card is still using the conventional method, namely by administrative officers making the value format in excel and then distributing it to each teacher. This process raises several problems, one of which is if there is a change in the value data, the teacher needs to contact the administrative officer first. In addition to the assessment process in the new student registration process, several problems are often encountered because the process is still done manually. Based on the problems that have been described, an information system will be developed that can facilitate the process of managing grades and registering new students using the waterfall software development method and Unified Modeling Language (UML) to model the system. At the requirements analysis stage, 40 functional requirements and 2 non-functional requirements were generated. At the system testing stage, several tests were carried out including black-box testing, compatibility testing, and UAT testing. In black-box testing, 20 test cases were produced with 100% valid results. In the compatibility test, it was found that in some browsers there were some minor issues caused by some browsers not supporting the CSS property used. In User Acceptance Testing, it shows that the information system built can be accepted by users with a value of 84.5% (Agree).